2014
DOI: 10.1586/14737140.2014.940326
|View full text |Cite
|
Sign up to set email alerts
|

The role of stereotactic body radiotherapy and stereotactic radiosurgery in the re-irradiation of metastatic spinal tumors

Abstract: Stereotactic body radiotherapy (SBRT) and stereotactic radiosurgery (SRS) are advanced radiotherapy delivery techniques that allow for the delivery of high-dose per fraction radiation. Advances in imaging technology and intensity modulation have allowed SRS and SBRT to be used for the treatment of tumors in close proximity to the spinal cord and cauda equina, in particular spinal metastases. While the initial treatment of spinal metastases is often conventional palliative radiotherapy, treatment failure is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Although there have been many reports on total spondylectomy and separation surgery for spinal tumors (6,9,11,13,(18)(19)(20)(21)(22), most of them have focused on the single treatment modality. With the development of medical technology, the treatment strategies of metastatic spinal tumors have changed over the years.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been many reports on total spondylectomy and separation surgery for spinal tumors (6,9,11,13,(18)(19)(20)(21)(22), most of them have focused on the single treatment modality. With the development of medical technology, the treatment strategies of metastatic spinal tumors have changed over the years.…”
Section: Discussionmentioning
confidence: 99%
“…First, the current state of the software used for automatic planning only provides options for de novo cases. However, it is not uncommon for patients undergoing spine SRS/SBRT to have already received palliative treatment at an earlier point in time 46 . Currently, we are working to incorporate that functionality, allowing the user to override the default dose limit to the spinal cord in terms of maximum dose allowed for the current plan or in terms of a combined biologically equivalent dose (BED).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not uncommon for patients undergoing spine SRS/SBRT to have already received palliative treatment at an earlier point in time. 46 Currently, we are working to incorporate that functionality, allowing the user to override the default dose limit to the spinal cord in terms of maximum dose allowed for the current plan or in terms of a combined biologically equivalent dose (BED). Second, the field setup using four co-planar full arcs and the mentioned collimation rotations, while used in this study and found to provide excellent dose shaping, is not a requirement.…”
Section: Structurementioning
confidence: 99%
“…Trials are underway to evaluate SBRTs efficacy in other disease sites, including advanced lung cancer, pancreatic cancer, sarcoma, and oligometastatic disease. Stereotactic body radiotherapy is also an attractive option in a re‐irradiation setting for spinal, thoracic, and head and neck cancers …”
Section: Opening Statementsmentioning
confidence: 99%